Neosartorya glabra polygalacturonase produced from fruit peels as inducers has the potential for application in passion fruit and apple juices - Vanessa Elisa Pinheiro; Carla Cristina Villela Desagiacomo; Michele Michelin; Alexandre Maller; Lummy Maria Oliveira Monteiro; João Atílio Jorge; Maria de Lourdes Teixeira de Moraes Polizeli (Brazilian Journal of Food Technology, 2017)
Summary Polygalacturonases are enzymes with the biotechnological potential for use in fruit juice clarification and for the enhancement of filtration efficiency. The aim of this work was to assess the production of polygalacturonase by the fungus Neosartorya glabra by means of solid-state and submerged fermentation using fruit peel residues as the carbon source, and also apply the enzyme in the clarification and decrease in viscosity of passion fruit and apple juices. The highest polygalacturonase (4.52 U/g/h) production was obtained by means of submerged fermentation in Vogel´s medium (1964) containing orange peel – Bahia variety (Citrus sinensis), at a concentration of 1.5% (w/v, dried mass) at 30-35°C for 72 h. The polygalacturonase of the crude extract presented optimal activity at 60°C and pH 5.5. The enzyme retained around 90% of the initial activity after 180 minutes at 40°C, and 50% of the initial activity after 150 minutes at 50°C. The enzyme was shown to be stable at acid pH values (3.0-6.5) after 120 minutes at 25oC. All these favourable enzymatic properties make the polygalacturonase attractive for potential uses in the industry of pectin-rich fruit juices, since the application of the crude extract to passion fruit (Passiflora edulis) juice caused an 80% reduction in viscosity and 75% decrease in light absorbance. In the processing of apple pulp juice (Malus domestica), there was a 50% reduction in viscosity and 78% decrease in light absorbance.